PENGARUH GAYA BELAJAR TERHADAP PEMAHAMAN MEMBACA PADA PELAJARAN BAHASA INGGRIS - Putri, Maharani (Ensiklopedia of Journal, 2018)
This research was aimed to find out the influence of students’ learning style toward their reading comprehension for second year of SMK YPM Zain Pauh Kambar Padang Pariaman in 2013/2014 academic year. This research was quantitative approach. The sample of this research was 62 students who were taken by using random sampling technique. The data were collected by using questionnaire and reading comprehension test. The data were analyzed by using regression technique with SPSS version 16.0 for windows. The research findings show that students’ learning style gave influence toward their reading comprehension.